A narrowing of meaning: loss of narrative unity and the nature of design change. (2014) - Walker, Stuart
This paper seeks to explore where design might best focus its efforts with respect to contemporary concerns about sustainability, particularly in view of the magnitude and nature of change required. The discussion traces the long entrenchment, over several centuries, of assumptions, conventions and outlooks that resulted in a shift in worldview from traditional to modern/late-modern. This shift is not only associated with unprecedented environmental damage, but also with a narrower perspective, a loss of narrative unity, and a loss of meaning. The argument is made that, by focusing on rationalistic, techno-scientific solutions design restricts its contribution to a variety of incremental changes that actually support the continuance of a fundamentally unsustainable system. Instead, design can widen its purview and be a catalyst for more substantive change by restoring a more balanced approach to products and processes in context; thereby contributing to a recovery of narrative unity and meaning.